2020
DOI: 10.1093/eurpub/ckaa124
|View full text |Cite
|
Sign up to set email alerts
|

Health professional mobility in the WHO European Region and the WHO Global Code of Practice: data from the joint OECD/EUROSTAT/WHO-Europe questionnaire

Abstract: WHO Member States adopted the Global Code of Practice on the International Recruitment of Health Personnel 10 years ago. This study assesses adherence with the Code’s principles and its continuing relevance in the WHO Europe region with regards to international recruitment of health workers. Data from the joint OECD/EUROSTAT/WHO-Europe questionnaire from 2010 to 2018 are analyzed to determine trends in intra- and inter-regional mobility of foreign-trained doctors and nurses working in case study destination co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 7 publications
(11 reference statements)
0
36
0
1
Order By: Relevance
“…The above-mentioned developments put healthcare workers and healthcare systems under pressure, resulting in numerous challenges: employee retention, attracting the new workers, burnout prevention and maintenance and/or improvement of service quality. Research [ 9 , 10 ] has also shown that healthcare workers are inclined to search for work abroad due to better conditions, supported by increased mobility driven by rising East–West and South–North intra-European migration, especially within the European Union—as is also the case in Slovenia. Failure to address these challenges will inevitably affect the healthcare system, as it is unlikely that simply training more healthcare workers will help to avoid a shortage given the continuing reduction in healthcare costs and increasing prevalence of expatriate healthcare staff [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The above-mentioned developments put healthcare workers and healthcare systems under pressure, resulting in numerous challenges: employee retention, attracting the new workers, burnout prevention and maintenance and/or improvement of service quality. Research [ 9 , 10 ] has also shown that healthcare workers are inclined to search for work abroad due to better conditions, supported by increased mobility driven by rising East–West and South–North intra-European migration, especially within the European Union—as is also the case in Slovenia. Failure to address these challenges will inevitably affect the healthcare system, as it is unlikely that simply training more healthcare workers will help to avoid a shortage given the continuing reduction in healthcare costs and increasing prevalence of expatriate healthcare staff [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…When LMICs face strong recommendations from international partners pushing for investment in a high-level medical education system, consideration should be given to what the country can afford and how greater equity and distribution of limited resources can be ensured in the longer term. In fact, the establishment of an ‘elite’ education system could result in the migration of local physicians to wealthier countries, since their education is not aligned with the economic condition in their own country [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Global migration has led to increases in doctors and patients with migration backgrounds [ 1 ]. They may experience difficulties in their host country, including communication problems, cultural differences, or discrimination.…”
Section: Introductionmentioning
confidence: 99%